Denying Difference to the Post-Socialist Other: Bernhard Heisig and the Changing Reception of an East German Artist - April A. Eisman (Contemporaneity: Historical Presence in Visual Culture, 2012)
This article traces the reception of East German artist Bernhard Heisig’s life and art—first in East Germany and then in the Federal Republic of Germany before and after the Wall. Drawing on post-colonial and post-socialist scholarship, it argues that Heisig’s reception exemplifies a western tendency to deny cultural and ideological difference in what the post-socialist scholar Piotr Piotrowski calls the “close Other.” This denial of difference to artists from the eastern bloc has shaped western understandings of Heisig’s life and art since reunification. Once perceived as an intellectually engaged, political artist, both in East and West Germany, after the fall of the Wall and German unification, Heisig was reinterpreted as a traumatized victim of two dictatorships, distorting not only our understanding of the artist and his work, but also of the nature of art and the role of the artist in East Germany.